Occurrence and risk factors associated with leptospirosis in dogs attended in a veterinary hospital in the semiarid of the Paraíba State, Northeast region of Brazil - Azevedo, Sérgio Santos de; Fernandes, Annielle Regina Fonseca; Queiroga, Inês Maria Barbosa Nunes; Alves, Clebert José; Morais, Zenaide Maria de; Santos, Carolina de Sousa Américo Batista; Vasconcellos, Sílvio Arruda (Brazilian Journal of Veterinary Research and Animal Science, 2011)
The occurrence of leptospirosis was investigated in dogs from Patos city, semiarid of Paraíba State, Northeast region of Brazil, and the risk factors associated with the infection were analyzed. One hundred and fifty two blood samples were collected from dogs attended in a veterinary hospital during July to November 2008. The diagnostic method carried out for leptospirosis was the microscopic agglutination test, using a batch of 24 leptospiral serovars. The frequency of seropositive animals was 19.73% (95% CI = 13.73% - 26.96%) and most frequent reactant serovars were Autumnalis (13.16%) and Grippotyphosa (1.97%). The multivariate logistic regression analysis showed that the risk factors for leptospirosis were mixed breed (odds ratio = 3.67; P = 0.009) and the contact with caprine/ovine (odds ratio = 10; P = 0.034).